NP-018 Building capacity within a Hepatitis C treatment model. The validation process for a Hepatitis C pre-treatment pharmacist assessment complex intervention toolkit. (14th March 2021) - Coghlan, M; O'Leary, A; Melanophy, G; Norris, S; Bergin, C
Abstract : Background and importance: The pre-treatment pharmacist assessment is a complex intervention toolkit (CIT) which has been designed to support devolvement of Hepatitis C (HCV) treatment to primary care providers including pharmacists. It combines all aspects of pre-treatment assessment into a proforma to ensure optimum HCV treatment selection. Aim and objectives: To assess the validity of the PTPA via a matched cohort study. Material and methods: Pharmacists were invited to participate in this study to review HCV case vignettes. Participants were divided into two groups using a concealed randomisation method (Group A = CIT use; Group B = case review as per current standard practice). A random sample of anonymised cases were selected from the Irish HCV treatment registry using selected co-variates (eg, fibrosis stage). A sample size of 56 cases per group was calculated. The primary endpoint was selection of the optimum treatment regimen. Secondary endpoints included time to completion, detection of drug-drug interactions (DDIs) and patient interventions. Statistical analysis was completed to assess variation between groups. Results: A total of 56 cases were completed per group. CIT use was associated with selection of optimum HCV treatment in 92.9% of cases, compared with 60.7% of cases in group B (p<0.05). DDI detection rates increased with CIT use (74.8% vs 47.1%; p<0.05). CIT users proposed an average of 3.5 interventions per case versus 2 interventions per case in Group B. The CIT was associated with a longer median completion time (20 versus 15 minutes, however this difference was not statistically significant (p 0.06). Conclusion and relevance: The findings of this study confirm the effectiveness of the CIT. The potential for pharmacists working in all practice environments in Ireland to make a robust contribution to HCV treatment, can be supported using this CIT. This type of capacity building is key to upscaling the model of care to achieve elimination targets. References and/or acknowledgements: Zhou K, Fitzpatrick T, Walsh N, Kim JY, Chou R, Lackey M, et al . Interventions to optimise the care continuum for chronic viral hepatitis: a systematic review and meta-analyses. The Lancet Infectious diseases 2016. Meyer JP, Moghimi Y, Marcus R, Lim JK, Litwin AH, Altice FL. Review: Evidence-based interventions to enhance assessment, treatment, and adherence in the chronic Hepatitis C care continuum. International Journal of Drug Policy 2015;26 :922–35. Craig P, Dieppe P, Macintyre S, Michie S, Nazareth I, Petticrew M. Developing and evaluating complex interventions: the new Medical Research Council guidance. BMJ (Clinical research ed). 2008;337 : a1655. Campbell NC, Murray E, Darbyshire J, Emery J, Farmer A, Griffiths F, et al . Designing and evaluating complex interventions to improve health care. BMJ (Clinical research ed). 2007;334 (7591):455–9.